EFEKTIVITAS BIAYA PENGGUNAAN ANTIBIOTIK PASIEN COVID-19 DI RUMAH SAKIT TADJUDDIN CHALID MAKASSAR - Andi paluseri; Rika Oktaviani; Zulfahmidah Zulfahmidah; Fajriansyah Fajriansyah (Media Farmasi XXX, 2021)
Cost-Effectiveness Analysis Of The Use Of The Antibiotics Levofloxacin And Azithromycin In Patients With Coronavirus Disease 2019Corona Virus Diseases 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome corona virus 2 (SAR-CoV-2) which causes respiratory infections. This disease requires a large cost in the management process. Therefore, this research aims to analyze the cost-effectiveness in the use of azithromycin and levofloxacin antibiotics in the treatment of COVID-19 at a General hospital in Makassar City.  This is an observational cross-sectional research with a prospective data collection method (January-March 2021) and a total sampling technique. Furthermore, data were taken from medical records and part of the financial information system, including patients' characteristics data (medical record number, patient initials, age, gender), clinical data (diagnosis, swab-test results), drug use data (dosage, rules of use, and duration of drug administration), and total medical costs (healthcare perspective: drug, treatment, laboratory, and radiology costs). Moreover, the effectiveness of this study was measured by the number of patients that were declared cured (negative swab-test). The results showed that the ACER value of the levofloxacin and azithromycin antibiotic were Rp. 191,705 and Rp. 157,359 respectively. These results indicate that the azithromycin antibiotic therapy group is more cost-effective compared to the levofloxacin group. Keywords   : Cost Effectiveness, COVID-19, Antibiotics.Corona Virus Diseases 2019 (COVID-19) merupakan penyakit menular yang disebabkan oleh severe acute respiratory syndrome corona virus 2 (SAR-CoV-2) yang dapat menyebabkan infeksi saluran pernapasan. Penyakit ini membutuhkan biaya besar dalam proses penatalaksanaannya. Penelitian ini bertujuan untuk menganalisis nilai cost-effectiveness penggunaan antibiotik azitromisin dan levofloksasin pada pengobatan COVID-19 pada salah satu Rumah Sakit Umum di Kota Makassar. Desain penelitian ini adalah observasional cross-sectional dengan pengambilan data secara prospektif (Januari-Maret 2021). Teknik pengambilan sampel pada penelitian ini adalah total sampling. Data diambil dari rekam medis pasien dan bagian sistem informasi keuangan pada salah satu Rumah Sakit Umum di Kota Makassar, meliputi data karakteristik pasien (nomor rekam medis, inisial pasien, umur, jenis kelamin), data klinis pasien (diagnosis, hasil swab-test), data penggunaan obat (dosis, aturan pakai, dan lama pemberian obat), data total biaya pengobatan (healthcare perspective: biaya obat, biaya perawatan, biaya laboratorium, biaya radiologi). Efektivitas dalam penelitian ini diukur dari jumlah pasien yang dinyatakan sembuh (hasil pemeriksaan swab-test dinyatakan negatif). Hasil penelitian menunjukan nilai ACER antibiotik levofloksasin sebesar Rp. 191.705 dan nilai ACER antibiotik azitromisin sebesar Rp. 157.359. Hasil ini menunjukan bahwa kelompok terapi antibiotik azitromisin lebih cos-effective dibandingkan dengan kelompok terapi antibiotik levofloksasin. Kata Kunci : Efektivitas Biaya, COVID-19, Antibiotik